PENGARUH CORPORATE GOVERNANCE, PROFITABILITAS DAN KONEKSI POLITIK PADA TAX AVOIDANCE - Utari, Ni Kadek Yuliani; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2017)
Efforts to reduce tax liabilities legally by utilizing the loophole on the tax regulations defined as tax avoidance. The purpose of thisestudy was to testsand providesempirical evidencesof the influencesof corporate governance, profitability and political connections on tax avoidance. The entire industrial companies and real’sestate properties listed on the StocksExchangesfor the period 2012-2015 the populations were taken. Method of selecting samples obtained through purposive sampling techniques in order to obtain 128 observasian. Multiple linear analysisewas usedsto analyzedthe research data. Based on the analysis, the proportion of independent directors and the existencesof an audit committeesas a proxy of corporate governance and no significant negative effect on tax avoidance. Profitability was measured using returnson assets and a significant negative effect’son tax avoidance, as wellsas political connections, as measured by a dummy variable positive and significant impacteon tax avoidance.
Keywords: Corporate governance, profitability, political connection, tax avoidance.